Pengaruh prinsip akuntabilitas dan transparansi terhadap kinerja pegawai - Aufa Moerrin, Dimas; Priono, Hero (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Achieving the best or consistent performance is not an easy matter and this is also experienced by PT Jasamitra Popertindo where organizational performance is still not optimal. The existence of performance problems at PT Jasamitra Propertindo is at least illustrated by the statement of one of the directors of PT Jasamitra Porpertindo, namely the Director of Human Resources and General Affairs, who said that there are still some employees who arrive late and some people are absent from work. Performance problems can also be seen from the realization of spending that is far from the set budget. In addition, BPIP is always serious about improving the implementation of bureaucraticreform and internal performance accountability. In order to create a capable and competitive bureaucracy, able to translate government programs effectively and efficiently. BPIP's ranks are encouraged to be more consistent and innovative based on performance. Organizational transformation is marked by more and more work units synergizing with other work units. Performance achievements related to Indonesia are synonymous with diversity. Every program and activity can be optimized to be felt directly by the community. This study aims to obtain empirical evidence of the effect ofaccountability and transparency on employee performance. The object of this research is PT. Jasamitra Propertindo with the number of employees who can be used as respondents as many as 25 people. The analysis technique for this research uses a smart Partial Least Square (PLS) 3.0 tool. Based on data analysis, it was found that accountability and transparency statistically have a positive and significant effect on employee performance so that these results are in accordance with the hypothesis proposed in the study.